2021
DOI: 10.1371/journal.pone.0253470
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome genes polymorphisms may influence the development of hepatitis C in the Amazonas, Brazil

Abstract: Hepatitis C is considered a major public health problem caused by the hepatitis C virus (HCV). Viral infections are known to induce production of IL1β through the signaling pathway of inflammasomes. Emerging evidences suggest that Inflammasome genes may influence the immune response against HCV as the host genetic background may contribute to the balance between acute and chronic inflammation. We investigated in 151 patients with chronic hepatitis C and 206 healthy blood donors’ individuals (HD). Polymorphisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
(46 reference statements)
0
3
0
1
Order By: Relevance
“…However, the genotypes associated with HCV infection susceptibility are diverse. While one study found that the C/C genotype was predominant in HCV-positive patients 42 , another reported that the C/T genotype was more prevalent in Wang et al's study (2003) 43 . Moreover, other research has concluded that the T/T genotype was a significant risk factor for the progression of chronic HCV infection to HCC 44 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the genotypes associated with HCV infection susceptibility are diverse. While one study found that the C/C genotype was predominant in HCV-positive patients 42 , another reported that the C/T genotype was more prevalent in Wang et al's study (2003) 43 . Moreover, other research has concluded that the T/T genotype was a significant risk factor for the progression of chronic HCV infection to HCC 44 .…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, other research has concluded that the T/T genotype was a significant risk factor for the progression of chronic HCV infection to HCC 44 . In addition, the mutant T/T allele has been frequently reported in patients with chronic HCV and HCV-induced liver cirrhosis 42 . An extensive inflammasome gene polymorphism study reported that the C allele of IL-1β rs16944 was less likely to advance hepatitis C development 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Purinergic receptors have been associated with HCV; thus, P2X4R regulates the secretion of micro-RNA containing exosomes by HCV-infected hepatocytes [ 18 ], and polymorphisms of genes encoding for inflammasome components, including AIM2, have been correlated to the development of C-hepatitis in Amazonia [ 19 ]. Higher expression levels of such molecules are found in blood samples of HCV patients compared to healthy blood donors’ individuals, with a positive association with the disease stage.…”
Section: Discussionmentioning
confidence: 99%
“…No presente estudo não foi encontrada associação significativa, após a análise multivariada, dos SNPs Q95H e Q244E com a esteatose hepática nos HCV (Cai et al, 2011;Coppola et al, 2015a;Eslam et al, 2016;Fan et al, 2016, Kralj et al, 2016. Além disso, estudos que avaliam os efeitos combinados entre polimorfismos na infecção pelo HCV têm se mostrado relevantes (Gao et al, 2017;Huang et al, 2017;Toro et al, 2021;Tao et al, 2022), uma vez que os polimorfismos podem contribuir para o desenvolvimento de doenças e comorbidades e alguns podem não ter funções independentes. Tao et al (2022), por exemplo, descreveram que polimorfismos nos genes Transporter associated with antigen processing (TAP) e HLA-I podem apresentar um efeito combinado na suscetibilidade à hepatite C crônica (Tao et al, 2022).…”
Section: Discussionunclassified